The Influence of Empowering Leadership and Adversity Quotient on Teacher Performance in Public Elementary Schools - Thoibah Thoibah; Dessy Wardiah; Andi Rahman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the influence of empowering leadership and adversity quotient (AQ) on teacher performance in public elementary schools, addressing persistent performance variations. The research employs a quantitative, correlational design. Data were collected from 95 teachers, selected via proportional random sampling from a population of 123, using validated and reliable instruments. Analysis was conducted using simple and multiple linear regression to test partial and simultaneous effects. The results confirm that both factors significantly enhance performance. Empowering leadership has a positive, significant effect (regression coefficient: 0.386), explaining 16.6% of variance. AQ also shows a positive, significant influence (coefficient: 0.321), contributing 10.3%. Together, they account for 30.6% of performance variance (F-value: 20.138), demonstrating a substantial combined impact. The novelty lies in concurrently investigating the synergy between a specific leadership style (empowering) and a psychological resilience construct AQ within an Indonesian elementary school context. A key practical implication is that school administrators should implement leadership training focused on empowerment while fostering programs to build teacher resilience, as their combination optimally boosts performance. The study contributes an empirically validated model highlighting that both external leadership support and internal psychological capacity are critical, interdependent levers for improving educational outcomes.